A query optimization algorithm for an object-oriented data model - Miranda, Mark Joel B. (Animo Repository, 1994)
Most query optimization algorithms have been designed for relational database systems to improve their performance in generating results for content-based queries. Object-oriented database systems presents a different way of managing a database. Research on query processing in object-oriented databases is still in its initial stage. This is the reason why it is one of the research issues of object-oriented database interest groups. A query optimization algorithm for an object-oriented database model is presented. This algorithm will perform optimization on queries that can be specified in the object-oriented database model. To support the algorithm, an object-oriented database model and an object-oriented algebra is also presented.